Nanocompósito contendo hexacianoferrato de cobalto/nanotubos de carbono/ácido fólico para a aplicação em terapia fotodinâmica visando o tratamento de câncer de mama. - Oliveira, Hellen Cristina Novais de (2025)
This study presents the synthesis of a ternary nanocomposite, HCFCo@NTCf@AF, developed through the coprecipitation method for application in photodynamic therapy (PDT), a minimally invasive approach for the treatment of triple-negative breast cancer, which is known for its high invasive and metastatic potential. The choice of components—Prussian blue analogs, functionalized carbon nanotubes, and folic acid—was based on their photosensitizing properties and biocompatibility. Characterization revealed an increase in the average particle size (SEM), the presence of all constituent elements (EDS), and the face-centered cubic structure of metal hexacyanoferrates (XRD). TGA analysis showed that the material lost a total of 45% water from its structure, which was further studied via Raman and FTIR, revealing the respective bands of the materials. Additionally, the voltammograms provided information on oxidation states and peaks corresponding to HCFCo. UV-Vis and diffuse reflectance spectra confirmed an absorption band in the visible region, potentially useful for tumor treatment by PDT. Cell viability assays with the MDA-MB-231 line showed that the isolated materials exhibited low cytotoxicity at the tested concentrations. Under red LED irradiation, the nanocomposite HCFCo@NTCf@AF induced 79% cell death at concentrations of 0.8 and 1.0 mg mL⁻¹, demonstrating significant photodynamic effect. Apoptosis data correlated with the phototoxicity results, confirming that the ternary nanocomposite showed the best performance in inducing cell death via late apoptosis of tumor cells. These results highlight the synergistic properties and potential of this nanocomposite as a promising candidate for the treatment of triple-negative breast cancer through PDT.